APLIKASI PENGGABUNGAN GAMBAR MENGGUNAKAN METODE TRANSLASI, ROTASI, DAN HISTOGRAM EQUALIZATION - Freddy Freddy (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Image processing is image processing, especially using a computer, the image quality becomes better. Due to the limitations of optical sensing device for capturing an object, then the object can not be taken in all the necessary decision-making so that the object several times. Method for combining multiple objects or pictures that have been taken into one unified image called image mosaic. The method used is the method of translation, rotation, and histogram equalization. The purpose of the translation method is to combine the four pieces of the image into the image of the whole, while the method of rotation is used to rotate the image if that image in a tilted state. Histogram equalization method is used so that the spread of colors in the image to be evenly distributed. The results of the test is the image that is to be whole and have a uniform spread of grayscale colors. Key words Histogram Equalization, Image Mosaic, Image Processing, Rotation, Translation.